Human rights and environmental justice: A legal framework for sustainable ecosystem management - Anas Akram Mohammed; Ibrahim Khilel Khinger; Omar Ahmed Hassan Khamees; Majid Fadhil Ziboon; Thamer Kadum Yousif Al Hilfi (Environment and Social Psychology, 2025)
The article discusses the human rights approach towards environmental justice and sustainable ecosystems governance. The urgency for integrative legislation that addresses environmental and social dimensions together has become acute with rising ecological malaise and social and environmental inequities. This study adopts a multidimensional methodology with a structured legal analysis, econometric modeling, comparisons between regional case studies, and scenario-based simulations. Based on data drawn from international treaties, national laws, environmental datasets, and judicial decisions in five regions of the globe, this allowed for an evaluation of the efficiency and institutional performance. The evidence shows stronger environmental benefits for jurisdictions where legal activation is robust, systems of compliance with the law are strict, and community participation is incorporated more organically into environmental governance. Statistical tests have shown that socioeconomic inequities, like income and education divides have a very close relationship with environmental harm, pointing to the need for the kind of redistributive legal frameworks. In addition, predictive modeling further ratifies that legal interventions translate into long-term ecological resilience coupled with increased indices of compliance. Comparative evidence from Bangladesh and the EU context supports this claim, showing that integrative legal frameworks not only enhance compliance but also create measurable improvements in ecosystem resilience and socio-environmental equity. The discussion provides recommendations for future research and policy development, such as expanding temporal modeling, incorporating indigenous legal systems, and aligning legal interventions with climate finance and biodiversity policies. This study further feeds into the emerging discourse on environmental human rights and provides evidence that can be used to tailor fair systems of law that are equally able to promote environmental sustainability as well as social justice.